Sequential intravesical gemcitabine and mitomycin C chemotherapy regimen in patients with non-muscle invasive bladder cancer - Breyer, Benjamin N. (2009)
OBJECTIVES: Currently, there are few options other than cystectomy for the management of BCG refractory non-muscle invasive bladder cancer. We report our experience with intravesical combination chemotherapy using gemcitabine and MMC in such patients. MATERIALS AND METHODS: We identified all patients with non-muscle invasive bladder cancer who were BCG refractory or intolerant and had been treated with intravesical gemcitabine and MMC at our institution. Patients were treated with a combination of intravesical gemcitabine (1000 mg in 50 ml sterile water) followed sequentially by intravesical MMC (40 mg in 20 ml sterile water) every week for 6 weeks (induction). Induction therapy was followed by a maintenance regimen using the same dose of gemcitabine and MMC once a month for 12 months. Data regarding patient demographics and disease information such as previous intravesical therapy, previous cystoscopy, cytology results, time to recurrence, and side effect profile were collected. RESULTS: A total of 10 patients (6 male and 4 female) aged 48 to 85 years (median 67 years) underwent treatment with a median follow-up of 26.5 months (4–34 months). Six patients were recurrence free and have maintained their response at a median of 14 months (4–34 months). Four patients had biopsy proven recurrence. Median time to recurrence was 6 months (range 4–13 months). The therapy was well tolerated in all patients. There were no major complications. Two patients experienced irritative lower urinary tract symptoms, which did not require cessation of therapy and one experienced a maculopapillary rash that improved with benadryl. CONCLUSIONS: In patients with recurrent BCG refractory bladder cancer, intravesical combination chemotherapy with gemcitabine and MMC appears to be well tolerated and yields a response in a good proportion number of patients.